2020
DOI: 10.1055/s-0040-1713158
|View full text |Cite
|
Sign up to set email alerts
|

Morphology at the Distal Radioulnar Joint: Identifying the Prevalence of Reverse Obliquity

Abstract: Abstract Background Recent advances in the understanding of ulnar-sided wrist pathologies such as ulnar abutment syndrome (UAS) have brought increased attention to the anatomy of the distal radioulnar joint (DRUJ). Previous work established three anatomical variants of the sigmoid notch (parallel, oblique, and reverse oblique). The reverse oblique DRUJ poses theoretical risk of increased contact forces following ulnar shortening osteotomy, a common method of treating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
5
0
3
Order By: Relevance
“…This has been highlighted in previous investigations with the prevalence of reverse obliquity morphology at the DRUJ. 2 Authors have suggested caution in using ulnar shortening osteotomy in this morphology. Moreover, our study confirms that sagittal alignment and translation at the DRUJ articulation are directly related to ulna bowing at the distal ulna.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been highlighted in previous investigations with the prevalence of reverse obliquity morphology at the DRUJ. 2 Authors have suggested caution in using ulnar shortening osteotomy in this morphology. Moreover, our study confirms that sagittal alignment and translation at the DRUJ articulation are directly related to ulna bowing at the distal ulna.…”
Section: Discussionmentioning
confidence: 99%
“…Conditions and injury to the components of this intricate joint can be devastating to patients. 1 , 2 , 3 , 4…”
mentioning
confidence: 99%
“…They also concluded that reverse oblique morphology correlated with ulnar-sided wrist pathology including DRUJ arthritis. 17 Kumar et al analyzed the volar surface of the uninjured distal radius using CT scans, and they showed that considerable variation occurs in volar surface curvature morphology. 18 In the current study, a smaller SNA, larger VT, and smaller LFCR were shown to be the possible risk factors for VLF occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…With a larger SNA in the AP radiograph, axial load from the lunate should be applied toward the radial bone axis. However, with a smaller SNA (reverse oblique type 17 ), it would be applied in the ulnar direction, which can result in fracture of the distal volar lip. A larger VT and smaller LFCR in the lateral radiograph means that the deep lunate facet is tilting in the volar direction.…”
Section: Discussionmentioning
confidence: 99%
“…Based on prior literature, there is a 14% incidence of asymptomatic radiographic DRUJ arthritis and 8% incidence of symptomatic DRUJ arthritis in patients who undergo TWA. 20 31 Using these two numbers, it would require 229 patients to reach 80% power of detecting symptomatic DRUJ arthritis requiring surgery after TWA. Additionally, although the present study reported adequate mid-term follow-up compared with other similar studies, longer follow-up may have identified more patients who experienced substantial DRUJ symptoms that would benefit from surgery.…”
Section: Discussionmentioning
confidence: 99%